A New Wide Bandgap Donor Polymer for Efficient Nonfullerene Organic Solar Cells with a Large Open‐Circuit Voltage. Issue 21 (29th August 2019) - Tang, Yumin; Sun, Huiliang; Wu, Ziang; Zhang, Yujie; Zhang, Guangye; Su, Mengyao; Zhou, Xin; Wu, Xia; Sun, Weipeng; Zhang, Xianhe; Liu, Bin; Chen, Wei; et al.
Abstract: Significant progress has been made in nonfullerene small molecule acceptors (NF‐SMAs) that leads to a consistent increase of power conversion efficiency (PCE) of nonfullerene organic solar cells (NF‐OSCs). To achieve better compatibility with high‐performance NF‐SMAs, the direction of molecular design for donor polymers is toward wide bandgap (WBG), tailored properties, and preferentially ecofriendly processability for device fabrication. Here, a weak acceptor unit, methyl 2, 5‐dibromo‐4‐fluorothiophene‐3‐carboxylate (FE‐T), is synthesized and copolymerized with benzo[1, 2‐b:4, 5‐b′]dithiophene (BDT) to afford a series of nonhalogenated solvent processable WBG polymers P1‐P3 with a distinct side chain on FE‐T. The incorporation of FE‐T leads to polymers with a deep highest occupied molecular orbital (HOMO) level of −5.60−5.70 eV, a complementary absorption to NF‐SMAs, and a planar molecular conformation. When combined with the narrow bandgap acceptor ITIC‐Th, the solar cell based on P1 with the shortest methyl chain on FE‐T achieves a PCE of 11.39% with a large V oc of 1.01 V and a J sc of 17.89 mA cm −2 . Moreover, a PCE of 12.11% is attained for ternary cells based on WBG P1, narrow bandgap PTB7‐Th, and acceptor IEICO‐4F. These results demonstrate that the new FE‐T is a highly promising acceptor unit to construct WBG polymers for efficient NF‐OSCs. Abstract : A series of wide bandgap donor polymers are designed and synthesized by incorporating a monothiophene functionalized with both a fluorine atom and an ester group. Fabricated from nonhalogenated solvent, power conversion efficiencies of 11.39% and 12.11% are achieved for binary and ternary nonfullerene solar cells, respectively.